Protective effect of serum carotenoids on mortality among metabolic syndrome patients: attenuated by lipid-lowering drugs - Chunxiang Li; Yanlan Liang; Qiuyuan Lu; Yuanxin Lin; Shifeng Wen; Xiaoyu Luo; Shiping Huang; Xue Zhong; ZhangJian Xu; Fei Wang (Nutrition Journal)
Abstract Background Limited evidence exists about the relationship between serum carotenoid and mortality in metabolic syndrome (MetS) patients, and the effects of medication use on this association remains unclear. Methods The study encompassed 2,521 MetS patients from the National Health and Nutrition Examination Survey (NHANES) 2001–2006 and 2017–2018. A total of 7 serum carotenoids were evaluated. Death data were sourced from the National Death Index, with causes assessed using ICD-10 codes. Bayesian kernel machine regression (BKMR) and random survival forest (RSF) were utilized to investigate serum carotenoid mixture on mortality and identify key carotenoids. “Qgcompint” R package was used to explore the modifying effects of medication use. Results The serum carotenoid levels at baseline ranged from 0.04 to 1.37 µmol/L. During a follow-up of 15.1 years, there were 696 deaths (27.61%), with 247 (35.49%) by cardiovascular disease (CVD), 148 (21.26%) by cancer, and 301 (43.25%) by other diseases. Individual and combined serum carotenoids were negatively associated with all-cause mortality (HR range:0.70–0.88, 95%CI range:0.56–0.99, all P < 0.05). α-carotene (VIMP = 0.223 in RSF) and lutein/zeaxanthin (PIP = 1.000 in BKMR) emerged as the greatest contributors to all-cause mortality. Lipid-lowering drugs attenuate the negative effect of serum carotenoids on MetS patients’ mortality (P int = 0.014). Conclusion The present study identified a protective effect of serum carotenoid on mortality in MetS patients, which was probably weakened by lipid-lowering drugs. Early dietary interventions for MetS patients taking lipid-lowering drugs, particularly those rich in carotenoids like α-carotene and lutein/zeaxanthin, could help reduce mortality.